The effect of economic growth volatility on income and wealth inequality in South Africa - Smith, Aarin J (Graduate School of Business (GSB), 2025)
This study uses a vector error correction model with impulse response, variance decomposition, and block Granger causality analysis over the period 1975-2018 to identify the effect of economic growth volatility on income inequality and wealth inequality in South Africa, and to determine whether this effect is more significant for income inequality or wealth inequality. The results show that economic growth volatility leads to long-term increases in both income inequality and wealth inequality with wealth inequality equalising at a higher level than income inequality. In addition, economic growth volatility is found to affect income inequality in the short- and medium-term and wealth inequality in the long-run. Furthermore, economic growth volatility is found to unidirectionally drive income inequality while population growth has a bidirectional causal association with income inequality. None of the factors are found to significantly drive wealth inequality but wealth inequality is found to drive population growth